Relationship between Perineal Hygiene Behavior and Reproductive Health in Adolescents Who Experience Early Marriage - Farida Lailatul Fitriyah; Titik Suhartini; Iit Ermawati (KHD Production, 2023)
Adolescence or puberty is a period of change in attitudes and behavior from childhood to young adulthood. Adolescence is the most beautiful adjustment period, and almost all adults go through this period with unforgettable memories. Still, it is often accompanied by upheavals and problems, both medical and psychological problems. This study analyzes the relationship between perineal hygiene behavior and reproductive health in adolescents who experience early marriage in Tandonsentul Village, Lumbang District, Probolinggo Regency. This research is quantitative with a correlational design using a cross-sectional study approach with 30 respondents using an accidental sampling technique. Data collection included coding, editing, and tabulating, then analyzed manually and by computer with Uji Spearman Rank. Based on data that out of 30 respondents, most perineal hygiene behaviors were lacking, 18 respondents (60%) with reproductive health in adolescents who experienced early marriage well, 0 respondents (0%) had good reproductive health, 13 respondents (43.3%) and those who less than 15 respondents (50%). The result of p-value=0.004 (a=0.05) shows a relationship between perineal hygiene behavior and reproductive health in adolescents who experience early marriage in Tandonsentul Village, Lumbang District, Probolinggo Regency. It is hoped that one of the efforts to increase the knowledge and behavior of adolescents regarding motivation to carry out premarital examinations correctly and adequately is to provide health education/health promotion.